Capabilities of contrast-enhanced ultrasound in angioneurology - A. O. Chechetkin; L. D. Druina (Анналы клинической и экспериментальной неврологии, 2017)
Contrast-enhanced ultrasound is a new promising direction inangio imaging, which has been increasingly used in clinical practicein recent years. We describe the history of the development ofthis method and consider in detail the basic physical and technicalprinciples of contrast-enhanced ultrasound as well as moderncapabilities of its use in diagnosis of various vascular diseases ofthe brain.